Two tissue-specific factors bind the erythroid promoter of the human porphobilinogen deaminase gene. - Mignotte, V (1989)
We have studied the erythroid-specific promoter of the human gene coding for Porphobilinogen Deaminase (PBGD) by DNaseI footprinting, gel retardation and methylation interference assays. We show that this promoter, which is inducible during MEL cell differentiation, contains three binding sites for the erythroid-specific factor NF-E1 and one site for a second erythroid-specific factor, which we name NF-E2. NF-E1 is a factor that also binds the promoter and the enhancer (present in the 3' flanking region) of the human beta-globin gene. NF-E2 has not yet been described and although it binds to a sequence containing the Ap1 consensus, it appears to be different from Ap1.